Do negative intrusive thoughts at diagnosis predict impaired quality of life, depressed mood and waking up with anxiety 3, 12 and 24 months after radical prostatectomy? – a longitudinal study. (3rd May 2020) - Bock, David; Angenete, Eva; Asplund, Dan; Bjartell, Anders; Carlsson, Stefan; Hugosson, Jonas; Stinesen Kollberg, Karin; Lantz, Anna; Nilsson, Hanna; Prytz, Mattias; Steineck, Gunnar; Thorsteinsdottir, Thordis; et al.
Abstract: Objective: To evaluate the effect of intrusive thoughts at diagnosis on quality of life, depressed mood and waking up with anxiety up to two years after radical prostatectomy. Method: The Laparoscopic Prostatectomy Robot Open (LAPPRO) trial was a prospective, longitudinal multicenter study of 4003 patients undergoing radical prostatectomy. Questionnaire data were collected preoperatively, at 3, 12 and 24 months after surgery. Results: The group of patients with intrusive thoughts at diagnosis had a statistically significant higher postoperative prevalence of impaired quality of life, depressed mood and waking up with anxiety as compared with the group of patients with no or minor intrusive thoughts. The highest risk increase for impaired QoL, depressed mood and waking up with anxiety ≥1/week was at 12, 3 and 3 months, respectively, where the three outcomes increased by 38% (RR: 1.38; 95%CI: 1.27–1.49)), 136% (RR: 2.36; 95%CI: 1.74–3.19)) and 165% (RR: 2.65; 95%CI: 2.22–3.17)), respectively. Conclusions: The demonstrated link between intrusive thoughts and quality of life, depressed mood and waking up with anxiety deliver is further evidence to the idea that intrusive thoughts has potential as an endpoint for assessing and predicting psychological distress among men with prostate cancer diagnosis. Trial registration number: ISRCTN06393679 (www.isrctn.com ). Date of registration: 07/02/2008. Retrospectively registered.